Ledipasvir/sofosbuvir treatment of hepatitis C virus is associated with reduction in serum apolipoprotein levels. Issue 12 (17th August 2015) - Younossi, Z.M.; Elsheikh, E.; Stepanova, M.; Gerber, L.; Nader, F.; Stamm, L.M.; Brainard, D.M.; McHutchinson, J.G.
Summary The interaction of lipoproteins with hepatitis C virus (HCV) has pathogenic and therapeutic implications. Our aim was to evaluate changes in the apolipoprotein profile of patients with chronic hepatitis C during and after successful cure with ledipasvir and sofosbuvir (LDV/SOF) with and without ribavirin (RBV). One hundred HCV genotype 1 patients who had achieved SVR‐12 after treatment with 12 weeks of LDV/SOF ± RBV were selected from the ION‐1 clinical trial. Frozen serum samples from baseline, end of treatment and week 4 of follow‐up were used to assay apolipoproteins (apoAI, apoAII, apoB, apoCII, apoCIII, apoE) using the Multiplex platform to assess for changes in the apolipoprotein levels. At the end of treatment compared to baseline, a significant reduction in apoAII levels (−14.97 ± 63.44 μg/mL, P = 0.0067) and apoE levels (−4.38 ± 12.19 μg/mL, P < 0.001) was noted. These declines from baseline in apoAII (−16.59 ±66.15 μg/mL, P = 0.0075) and apoE (−2.66 ± 12.64 μg/mL, P = 0.015) persisted at 4 weeks of post‐treatment follow‐up. In multivariate analysis, treatment with LDV/SOF + RBV was independently associated with reduction in apoE (beta = 5.31 μg/mL, P = 0.002) (compared to RBV‐free LDV/SOF) (P < 0.05). In contrast, apoCII levels overall increased from baseline to end of treatment (+2.74 ±11.76 μg/mL, P = 0.03) and persisted at 4 weeks of follow‐up (+4.46 ± 12.81 μg/mL from baseline, P = 0.0005). Subgroup analysis revealed an increase in apoCII during treatment only in patients receiving LDV/SOF without RBV (+5.52 ± 11.92 μg/mL, P = 0.0007) but not in patients receiving LDV/SOF + RBV (P = 0.638). Treatment with LDV/SOF ± RBV is associated with a persistent reduction in the apolipoprotein AII and E after achieving cure. These data suggest that treatment with LDV/SOF ± RBV may be associated with alterations in serum apolipoproteins which could potentially impact viral eradication.